ANALISIS PERBANDINGAN VOLUME PERDAGANGAN SAHAM (TVA), BID ASK SPREAD DAN RETURN SAHAM SEBELUM DAN SESUDAH PEMECAHAN SAHAM(STOCK SPLIT)-STUDY PADA PERUSAHAN YANG GO PUBLIC DI BURSA EFEK INDONESIA PERIODE 2010-2015 - Diyan Muji Riskiyani, 12.05.51.0009 (Students Journal of Economic and Management, 2016)
This study aimed to analyze the liquidity of the stock is proxied by trading volume activity, bid ask spread, stock returns before and after the announcement of stock split policy on companies that do stock splits listed in Indonesia Stock Exchange 2010-2015. In this study, the liquidity of the stock is proxied by trading volume activity, bid ask spread, stock returns before and after the stock split. Data were taken 54 companies that conduct stock split policy in Indonesia Stock Exchange 2010-2015. The data used is secondary data with data collection documentation. Data analysis using SPSS 22 software and menunggunakan Test Paired t test with 95 percent confident level (Î± = 0.05) to test the hypothesis. The results showed that there are significant differences between the average stock trading volume and bid ask spread for twelve days before and twelve days after the stock split. As for the variable stock returns before and after the stock split was not a significant difference. Keywords: liquidity, return, stock split, trading volume activity, bid ask spread, stock returns